2012
DOI: 10.3174/ajnr.a3377
|View full text |Cite
|
Sign up to set email alerts
|

Normal Flow Signal of the Pterygoid Plexus on 3T MRA in Patients without DAVF of the Cavernous Sinus

Abstract: BACKGROUND AND PURPOSE:Cavernous sinuses and draining dural sinuses or veins are often visualized on 3D TOF MRA images in patients with dural arteriovenous fistulas involving the CS. Flow signals may be seen in the jugular vein and dural sinuses at the skull base on MRA images in healthy participants, however, because of reverse flow. Our purpose was to investigate the prevalence of flow signals in the pterygoid plexus and CS on 3T MRA images in a cohort of participants without DAVFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…High signals originating from the reverse flow are frequently seen on 3-Tesla MRA [4]. Previous studies found a high signal in the CS on MRA in 43 (10.6%) of 406 healthy participants [4].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…High signals originating from the reverse flow are frequently seen on 3-Tesla MRA [4]. Previous studies found a high signal in the CS on MRA in 43 (10.6%) of 406 healthy participants [4].…”
Section: Introductionmentioning
confidence: 92%
“…High signals originating from the reverse flow are frequently seen on 3-Tesla MRA [4]. Previous studies found a high signal in the CS on MRA in 43 (10.6%) of 406 healthy participants [4]. These findings are considered to indicate flow signals in the PP/emissary vein (EV) originating from the reverse flow, as in the internal jugular vein (IJV) and SS.…”
Section: Introductionmentioning
confidence: 98%
“…The lack of hemodynamic information, however, limits their clinical usefulness (2)(3)(4). While four-dimensional (4D) contrast material-enhanced MR angiography at 3 T appears to be reliable and provides hemodynamic information on intracranial dural AVFs (5), it poses risks associated with contrast agents (6).…”
Section: Study Populationmentioning
confidence: 99%
“…In this case, the left sigmoid to inferior petrous sinus was depicted on ASL-based 4D-MRA image. On a previous study on 3T time-of-flight (TOF) MRA, 10 this finding may be the result of flow reversal. The other venous structures including the superior sagittal sinus were not depicted on ASL-based 4D-MRA images.…”
Section: Discussionmentioning
confidence: 90%